2005
DOI: 10.1039/b506442b
|View full text |Cite
|
Sign up to set email alerts
|

Self-organization of a sulfonamido-porphyrin in Langmuir monolayers and Langmuir–Blodgett films

Abstract: Langmuir monolayers (LM) and Langmuir-Blodgett (LB) films of pure lipophilic meso-tetra(4-dodecylaminosulfophenyl)porphyrin (PC12) and mixed with the anionic surfactant sodium hexadecylsulfate (SHS) were studied. The molecular packing and structure of PC12 and PC12-4SHS with variable surface pressure were investigated by surface pressure-area measurements, steady-state absorption, fluorescence emission and anisotropy, as well as by fluorescence lifetime imaging microscopy (FLIM). At low surface pressure, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Applications in forensic science, 10 combustion research, 11 microfluidic systems, [12][13][14][15] artworks 16 and lipid order problems in physical chemistry 17,18 have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Applications in forensic science, 10 combustion research, 11 microfluidic systems, [12][13][14][15] artworks 16 and lipid order problems in physical chemistry 17,18 have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…FLIM has been a privileged technique in our group to further investigate the interaction of porphyrinoids in supramolecular and nanostructured systems that include micelles [ 89 , 115 ], liposomes [ 92 ], molecular self-aggregates [ 34 , 43 ], Langmuir-Blodgett films [ 168 ], dendrimers [ 21 ], polyelectrolyte microcapsules [ 89 , 90 , 169 ], carbon nanotubes [ 39 ], graphene oxide [ 40 ], and gold nanostructures [ 150 , 152 , 154 , 155 , 156 ], as highlighted in some examples previously described in this review.…”
Section: Supramolecular Self-assemblymentioning
confidence: 99%
“…However, applications in diverse areas such as forensic science (Bird et al, 2007), combustion research (Ehn et al, 2011;Ni and Melton, 1996), luminescence lifetime mapping in diamond (Liaugaudas et al, 2009(Liaugaudas et al, , 2012, microfluidic systems (Benninger et al, 2005a(Benninger et al, , 2006Elder et al, 2006;Graham et al, 2010;Magennis et al, 2005;Robinson et al, 2008), art conservation (Comelli et al, 2004(Comelli et al, , 2005, remote sensing (Esposito, 2012;Ge et al, 2012;Lin et al, 2012), lipid order problems in physical chemistry (Togashi et al, 2005), the spatial distribution of dopants in perovskite oxides (Rodenbücher et al, 2013) and temperature sensing (Bennet et al, 2011;Benninger et al, 2006;Graham et al, 2010;Mendels et al, 2008;Okabe et al, 2012) have also been reported. FLIM has been carried out from the UV (Li et al, 2004;Schüttpelz et al, 2006) to the near infrared (Becker and Shcheslavskiy, 2013) and it is not surprising that fluorescence lifetime-based imaging is widely used in the biomedical sciences, and that this trend shows no signs of abating.…”
Section: Introductionmentioning
confidence: 98%